The more we sell the happier we are: Comparison of responsible alcohol service in trained and untrained establishments in Perth - Alexander, Nevil (2005)
This research investigated whether training licensees and approved managers of Perth pubs and taverns resulted in more Responsible Alcohol Service (RAS). Specifically it investigated whether apparently intoxicated customers were refused service. Trained and untrained premises were compared using two methods. Quantitative data was gathered by observers posing as intoxicated customers (pseudo-drunks) while qualitative data was collected during interviews with management, staff, and patrons of trained and untrained premises. No significant difference in the service of alcohol to intoxicated patrons in trained or untrained premises was found. The interviews revealed no distinction between the attitudes and beliefs of management, staff, or patrons of trained or untrained outlets. A majority of management and staff was aware of laws prohibiting service of alcohol to intoxicated people but acknowledged that in many instances intoxicated customers continue to be served. A number of reasons or excuses were proffered. One frequently cited excuse was if we don't serve drunks someone else will, so why shouldn't we profit from them? Communities incur considerable costs in both financial and social contexts from the harms associated with excessive alcohol consumption. One means of reducing the severity and frequency of these harms is to limit the consumption of individuals during drinking sessions. Licensed premises have been identified as having a significant role to play in achieving this outcome. The director of liquor licensing in Western Australia has mandated Responsible Alcohol Service training for licensees and approved managers. This research studied the efficacy of the training. While the importance of enlisting the help of management in attempts to introduce RAS programmes has been identified in previous research, this is the first time the efficacy of training management alone has been studied. This paper contributes to the body of knowledge of what works in a practical sense by identifying perceived shortcomings of the current training programs and suggesting remedies to those shortcomings. It makes recommendations for future research which will contribute to a deeper understanding of the problem